2017
DOI: 10.1126/sciadv.1601315
|View full text |Cite
|
Sign up to set email alerts
|

The nearly universal link between the age of past knowledge and tomorrow’s breakthroughs in science and technology: The hotspot

Abstract: Papers or patents that cite past work of a particular age distribution double their chances of being a hit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(78 citation statements)
references
References 33 publications
(85 reference statements)
5
68
0
Order By: Relevance
“…Several different research fields have also examined characteristics of highly cited papers and found significant differences between disciplines (e.g., Puuska et al, ; Waltman & van Eck, ). A recent study examined “content” differences between highly cited and low‐citation papers and found that highly cited papers contain discussions of both old and new research (Mukherjee & Romero, ). They found the “hot spot” for high‐citation papers was when a paper's cited references (CRs) had a low mean age (e.g., preferentially cited “new” work) and a high mean age variance (also cited seminal work from the past).…”
Section: Introductionmentioning
confidence: 99%
“…Several different research fields have also examined characteristics of highly cited papers and found significant differences between disciplines (e.g., Puuska et al, ; Waltman & van Eck, ). A recent study examined “content” differences between highly cited and low‐citation papers and found that highly cited papers contain discussions of both old and new research (Mukherjee & Romero, ). They found the “hot spot” for high‐citation papers was when a paper's cited references (CRs) had a low mean age (e.g., preferentially cited “new” work) and a high mean age variance (also cited seminal work from the past).…”
Section: Introductionmentioning
confidence: 99%
“…They hereby introduce the distance to the science frontier as a metric for science-technology intensity Watzinger and Schnitzer (2018). borrow this metric and provide correlations between the science-technology intensity and the value of patents Mukherjee et al (2017). emphasize the importance of the age structure of references.…”
mentioning
confidence: 99%
“…Trying to track all publications to build our work would not be viable because of the exponential growth of scientific literature (Mukherjee et al 2017). Many researchers have developed different approaches to predict an article's future citations and forecast which kind of literature is more likely to attract scientists' responses.…”
Section: Prediction Methods Of Citation Impactmentioning
confidence: 99%